Design and Analysis of Supporting Sleeve Manipulator based on Shear Link Mechanism - Yanwei Cheng; Qiang Zhang; Zhanli Wang; Hao Zhang; Wanxi Liu (Jixie chuandong)
In order to realize the function that the flexible silicone isolator can automatically open along the preset track， a kind of supporting sleeve manipulator based on shear linkage mechanism is designed. The overall scheme of the support sleeve manipulator and the shear link mechanism are designed and studied， the kinematics equation of the shear link mechanism is established， the motion track of the center of mass of the support and grip rod is simulated， and the motion simulation is analyzed by using Adams software. Simulation results show that the designed braced manipulator can meet the trajectory output requirements， and there is no interference in the supporting process and the operation is stable， which lays a foundation for the optimization design of the support manipulator in the next step.